Prediksi Epitop Antigenik sebagai Kandidat Vaksin Berbasis Peptida pada African Swine Fever Virus dengan Target P30 dan P72 - Difa Fitrah Kusumaningrum; Siti Kurniawati; Azizah Husnul Subagyo; Bintang Fajar Prayitno; Keisha Rama Diwangga; Miftahul Jannah; Jessica Ivana Alexandra Tasumo (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2026)
African Swine Fever Virus (ASFV) remains a critical global threat to swine health, demanding innovative vaccine strategies beyond currently limited live-attenuated options. This study employed an immunoinformatics-driven, in silico approach to identify antigenic B-cell epitopes from two key ASFV immunogens, P30 (CP204L) and P72 (B646L), as potential peptide-based vaccine candidates. Amino-acid sequences were retrieved from NCBI and modeled via SWISS-MODEL to predict structural exposure. Linear B-cell epitopes were mapped using IEDB BepiPred 2.0 and further screened for antigenicity and allergenicity using VaxiJen and AllerTOP. P30 exhibited broader surface-exposed epitope distribution and higher predicted immunogenicity, with QYGKAPDF emerging as the most promising non-allergenic antigenic peptide. In contrast, P72 displayed fewer, more conserved epitopes consistent with its compact capsid topology, with PREEYQPSGHIN identified as the best candidate based on immunogenic and non-allergenic properties. Comparative analysis highlights P30 as the superior immunogenic target, although combining both epitopes may enhance protective efficacy through complementary immune activation and structural stability. These findings provide a foundational framework for designing multi-epitope ASFV subunit vaccines and warrant subsequent experimental validation to support development of safe, effective, and durable ASFV immunoprophylaxis.